2005
DOI: 10.1590/s0100-41582005000100008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Brazilian strains of Xanthomonas campestris pv. viticola by rep-PCR fingerprinting

Abstract: Bacterial canker of grapevine (Vitis vinifera), caused by Xanthomonas campestris pv. viticola was first detected in Brazil in 1998, affecting grapevines in the São Francisco river basin, state of Pernambuco. The disease was also reported in Juazeiro, Bahia and later in Piauí and Ceará. Due to its limited geographical distribution and relatively recent detection in Brazil, very little is known about the pathogen's biology and diversity. Repetitive DNA based-PCR (rep-PCR) profiles were generated from purified ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
0
13
1
1
Order By: Relevance
“…Our results of rep-PCR also indicated that A* and A w types were close to A types, but they were excluded from A types in this combined analysis. Trindade et al (2005) argued that dendrograms obtained with REP, ERIC Fig. 1 Dendrogram showing relationships among Xanthomonas strains causing CBC based on combined analysis of ERIC-, BOX-and REP-PCR results.…”
mentioning
confidence: 99%
“…Our results of rep-PCR also indicated that A* and A w types were close to A types, but they were excluded from A types in this combined analysis. Trindade et al (2005) argued that dendrograms obtained with REP, ERIC Fig. 1 Dendrogram showing relationships among Xanthomonas strains causing CBC based on combined analysis of ERIC-, BOX-and REP-PCR results.…”
mentioning
confidence: 99%
“…Only the reproducible bands ranging from 0.2 to 3 kb were scored. Since combined analysis of rep-PCR primers showed a significant increase in differentiation capacity in other works (Trindade et al 2005;Lee et al 2007), combined data generated from two sets of primers were combined and then subjected to analysis. To estimate the genetic relationship among the strains, the similarity coefficient for pairs of isolates was calculated with Dice's coefficient index (Dice 1945).…”
Section: Discussionmentioning
confidence: 99%
“…d Sau96I: Lane M is 50 bp molecular size marker, Lane 1 is uncut product, Lane 2 is Xp21 (Xapf), Lanes 3-10 are Xp7, Xp17, Xp12, Xp11, Xp18, Xp2, Xp13 and Xp20, Lane 11 is negative control World J Microbiol Biotechnol (2011) 27:2371-23782375 polymorphism among Brazilian X. campestris pv. viticola strains and allowed their separation into five subgroups, although no correlation could be found with cultivar, geographic location or year of origin (Trindade et al 2005).…”
Section: Discussionmentioning
confidence: 99%